2002
DOI: 10.1038/sj.bjc.6600050
|View full text |Cite
|
Sign up to set email alerts
|

The free β-subunit of human chorionic gonadotropin as a prognostic factor in renal cell carcinoma

Abstract: The free b-subunit of human chorionic gonadotropin b is expressed in several nontrophoblastic tumours and this is usually associated with aggressive disease. Little is known about human chorionic gonadotropin b expression in renal cancer. We determined the pretreatment levels of human chorionic gonadotropin b in serum of patients with renal cell carcinoma, and studied whether elevated levels predicted the clinical outcome. Serum samples were collected before surgery from 177 patients with renal cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 25 publications
0
31
0
5
Order By: Relevance
“…In searching for intermediates of major metabolic pathways, an isoenzyme of pyruvate kinase has been suggested as a biomarker; however, enzymatic levels are variable and have a low sensitivity for nonmetastatic RCC (29 -31). Vinculin, human chorionic gonadotropin-␤, nuclear matrix proteins, metallothioneins, serum ferritin, matrix metalloproteinase activity, and many other proteins that are upregulated in tumor progression have also been suggested as [32][33][34][35][36][37]. These markers, however, have not proved useful in the clinical treatment of RCC patients because they lack specificity for RCC and/or require tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In searching for intermediates of major metabolic pathways, an isoenzyme of pyruvate kinase has been suggested as a biomarker; however, enzymatic levels are variable and have a low sensitivity for nonmetastatic RCC (29 -31). Vinculin, human chorionic gonadotropin-␤, nuclear matrix proteins, metallothioneins, serum ferritin, matrix metalloproteinase activity, and many other proteins that are upregulated in tumor progression have also been suggested as [32][33][34][35][36][37]. These markers, however, have not proved useful in the clinical treatment of RCC patients because they lack specificity for RCC and/or require tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Purified B11-hCG␤ fusion protein was subjected to SDS-PAGE on 4 Preparation of Monocyte-Derived DCs. Peripheral blood mononuclear cells were suspended in RPMI 1640 medium (Invitrogen, Carlsbad, CA) supplemented with 10% fetal bovine serum, 40 g/ml gentamicin, and 50 M ␤-mercaptoethanol.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the preoperative serum concentration of hCG␤ is a prognostic indicator in RCC independent of stage and grade, 19 but the prognostic significance of hCG␤ tissue expression is not known. We have now developed a quantitative reverse transcriptionpolymerase chain reaction (RT-PCR) method for quantification of the mRNAs for the two groups of hCG␤ genes and compared the expression levels with clinicopathological data.…”
mentioning
confidence: 99%